Respuesta :
Assuming that these equations depend on each other, We can use substitution to figure out what x is equal to. Since both equations have a certain value of x equal to y, we can substitute one of the equations into the other.
y = x - 1
Use substitution
x - 1 = 2x + 1
x = 2x + 2
-x = 2
x = -2
First, we replace y with the first equation, so it would look like this:
[tex] x - 1 = 2x + 1 [/tex]
Then we start simplifying:
[tex] x-2x = 1+1 [/tex]
At last we do:
[tex] -x = 2 [/tex] or [tex] x = -2 [/tex]
So the answer is: -x = 2 or x = -2
Hope this helped! c: